ANALISIS UJI PERSEPSI: Intonasi Kalimat Perintah Bahasa Indonesia oleh Penutur Bahasa Jepang - Susi Herti Afriani (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2015)
This study aims to analyze the intonation of a foreign speaker (a native speaker of Japanese) in uttering sentences of Indonesian command. The Tested is whether the intonation of Indonesian commands are uttered by speakers of Japanese grateful or not by a native speaker of Indonesian. This research is a descriptive qualitative research with a phonetic approach, using software praat, which describe the sound of suprasegmental (prosodic) directly related to the characterization of the sentence intonation of Indonesian such as intonation pattern, the group pauses, contour (prakontur/primary contour). Characteristics of Indonesian command line mode by speakers of Japanese is a tendency declination on the final pitch line and ride (experienced inclination) to the predicate.